Systematic review of treatment methods for recurrent varicoceles to compare post-treatment sperm parameters, pregnancy and complication rates - Cayan, Selahittin; Orhan, Irfan; Akbay, Erdem; Kadioglu, Ates (Wiley, 2019)
We aimed to define which method would be the best for the treatment of recurrent varicoceles. We analysed 21 studies to compare post-treatment improvement in semen parameters, spontaneous pregnancy and complication rates between the treatment methods. Overall spontaneous pregnancy rate was significantly higher in the surgical methods (44.3%) than in the radiological interventions (17.9%; p = .007). Post-treatment improvement rates in sperm parameters were significantly higher in the open surgical methods (77.5%) than in the radiological interventions (62.5%; p = .032). Post-treatment recurrence rates were 3.8% in the open surgical methods, 17.6% in the laparoscopic surgery and 3.3% in the radiological interventions. However, technical failure rate was 11.8% in the radiologic interventions. To analyse open surgical methods, recurrence rate was 0.6% in the microsurgical methods and 19% in the macroscopic methods, revealing significant difference (p < .001). Post-treatment testicular atrophy rate was significantly higher in the laparoscopic surgery (2.9%) than in the open surgery (0.3%; p = .033). In conclusion, surgical methods have higher pregnancy rates and higher improvement rate in sperm parameters than radiological interventions for the treatment of recurrent varicocele. Microsurgical redo varicocelectomy has lower recurrence and testicular atrophy rates than macroscopic varicocelectomy series. Therefore, patients with recurrent varicoceles should be informed based on these findings.
Keywords: complications; methods; pregnancy; recurrence; varicocele